“Green” Financing and EsG: Opportunity for sustainable socio-Economic Development - N. N. Semenova; I. A. Ivanova; O. I. Eremina (Финансы: теория и практика)
The implementation of the sustainable development strategy and the formation of a “green” economy model provide for the reorientation of financial resources, accounting by economic entities and public authorities and management of ESG-principles and the development of “green” financing tools.The purpose of the paper is to develop theoretical provisions and modeling of the impact of “green” financing on the socio-economic development of the subjects of the Russian Federation.Methods of data mining were used with temporary delays and corresponding lags responses of endogenous indicators, as well as cluster and correlation analysis. The result of the study was the specification of the economic content of the definition of “green” financing, as well as the construction of econometric models of the degree of interrelationship between “green” financing and the socio-economic development of the regions of Russia. The authors described the economic content of the definition of “green” financing, developed econometric models of the degree of interdependence of “green” financing and socioeconomic growth of Russia’s regions, calculated an integral indicator of sustainable socio-economic development of the regions of the Russian Federation taking into account ESGfactors (social risks, environmental risks, quality of management). Clustering of Russian regions according to the level of influence of “green” financing on their socio-economic development has also been carried out.The article concludes that the relationship between the level of socio-economic development of the regions of the Russian Federation and the volume of “green” financing is direct, strong, and can be expressed by increasing linear regression. The prospects for further research may be related to the assessment of the real needs of the volumes of “green” financing in the context of ensuring sustainable economic growth.